2010
DOI: 10.1007/s10439-010-9909-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Collagen and Glucose Modulated Cell Growth within Tissue Engineered Scaffolds

Abstract: The strategy of tissue engineering includes seeding cells onto porous scaffolds. The cellular construct is cultured in vitro for a period of time before transplantation for the patient. Because of the intrinsic complexity of biological systems, it is valuable to have models of simulation that can assess the culture conditions and optimize experiments. This work presents a mathematical model to account for the effects of glucose and type II collagen on chondrocyte growth under static culture conditions. Depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The model presented here extends previous models that have examined ECM synthesis and nutrient consumption (Chung and Ho, 2010; Dimicco and Sah, 2003; Nikolaev et al, 2010; Obradovic et al, 2000; Sengers et al, 2004a; Sengers et al, 2004b, 2005; van Donkelaar et al, 2011). In the model employed here, glucose was selected as the limiting nutrient.…”
Section: Discussionsupporting
confidence: 65%
“…The model presented here extends previous models that have examined ECM synthesis and nutrient consumption (Chung and Ho, 2010; Dimicco and Sah, 2003; Nikolaev et al, 2010; Obradovic et al, 2000; Sengers et al, 2004a; Sengers et al, 2004b, 2005; van Donkelaar et al, 2011). In the model employed here, glucose was selected as the limiting nutrient.…”
Section: Discussionsupporting
confidence: 65%
“…Figure 6a, b shows the steady-state glucose concentration distribution for a Schmidt number of Sc = 1,000 for s = 4R and s = 3R, respectively. An adequate supply of glucose is also required for the growth of cells, especially for the Chondrocytes growth (Chung and Ho 2010). In general, the distributions of the glucose concentration contours are very similar to those given in Fig.…”
Section: Resultssupporting
confidence: 57%
“…The design of the scaffold has been motivated by results in the literature which indicated that cell growth in scaffolds may be significantly limited by nutrient delivery as the void space inside the scaffolds is gradually occupied by cells, thereby restricting nutrient transport to the interior of the scaffold (Freed et al, 1994). Recent work by Chung and Ho (2010) suggests that internal seeding of cells in the interior of a scaffold may lead to better cell amounts and uniformities within the scaffold. The smaller diameter of the interconnecting channels may be varied to promote cell adhesion (Green et al, 2002;, while the larger pore diameter in the interior region of the scaffold may be optimized to promote cell migration and proliferation .…”
Section: Introductionmentioning
confidence: 98%